SOCIAL ECONOMIC ANALYSIS OF THE TOURISM SECTOR - Musliha (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: The tourism sector has now developed into the largest industry for economic growth in Indonesia; this can be seen from the increasing development of the number of tourist visits, both domestic and foreign tourists. The purpose of this study was to determine the impact of the existence of the Sikembang Park tourist attraction on the socioeconomics of business actors in Kembanglangit Village. Methods: The method used in this study is a descriptive method with a qualitative approach. Results: The results of this study are that the Sikembang Park tourist attraction has a positive impact in terms of economy and socio-culture. The economic impact is to increase income and create jobs and business opportunities. As well as the impact on the social life, namely a closer relationship between the people of Kembanglangit Village.Conclusion and suggestion: Based on the discussion regarding the Impact of the Existence of the Sikembang Park Tourism Object on the Socio-Economic Condition of Business Actors in Kembanglangit Village, it can be concluded that the existence of the Sikembang Park tourism object has a positive impact on the community's economic activities which consist of increasing income and opening up job opportunities and business opportunities. Communities around tourist sites get additional work as food and beverage traders. In addition, the Sikembang Park tourist attraction also has an impact on the social life of the Kembanglangit Village community, namely by creating a closer relationship between the people in Kembanglangit Village.